Convenient Synthesis of Acyclic Guanidines from Isothiouronium Iodides and Amines without Protection of the Amino Groups - Aoyagi, Naoto; Furusho, Yoshio; Endo, Takeshi (Synlett, 2014)
Acyclic guanidines were obtained in one step by reaction of isothiouronium iodides with an equimolar amount of various amines in tetrahydrofuran. The reactions proceeded under ambient conditions without N-protection/deprotection to afford the corresponding substituted guanidines in quantitative yields.
Keywords: guanidines; synthetic methods; amines; nucleophiles; substitution